Konsep Pendidikan Etika Sufistik-Filosofis Al-Ghazâlî - Sahid Sahid HM (Universitas Islam Negeri Mataram, 2011)
The study focuses on the ethic concept of al-Ghazâlî in education. The approach used by al-Ghazâlî, in relation to the educational ethic, is sufistic-philosopichal which tends to the concept of ma‘rifat Allâh, taqarrub, and tahassub through riyâdlah. These three dimentions are the main basis of how to educate the moslem’s ethic. For those whose spiritual has not been good yet, they are suppossed to learn constantly. Therefore, an educator may guide and bring spiritually the students to be close to Allah. In fact, al-Ghazâlî’s concept of ethic in education by sufistic-philosopichal approach has theoretically and practically broad influences for the moslem life all over the world. Such two influences indicate that practically and theoretically al-Ghazalî’s school of thought in ethical education turns out to be the basic of further thinking. Thus, the very strong al-Ghazalî’s influence toppled down the sufism at that time.